An Anatomical Study Comparing Two Surgical Approaches for Isolated Talonavicular Arthrodesis. (October 2014) - Higgs, Zoe; Jamal, Bilal; Fogg, Quentin A.; Kumar, C. Senthil
Background: Two operative approaches are commonly used for isolated talonavicular arthrodesis: the medial and the dorsal approach. It is recognized that access to the lateral aspect of the talonavicular joint can be limited when using the medial approach, and it is our experience that using the dorsal approach addresses this issue. We performed an anatomical study using cadaver specimens, to compare the amount of articular surface that can be accessed by each operative approach. Methods: Medial and dorsal approaches to the talonavicular joint were performed on each of 11 cadaveric specimens (10 fresh frozen, 1 embalmed). Distraction of the joint was performed as used intraoperatively and the accessible area of articular surfaces was marked for each of the 2 approaches using a previously reported technique. Disarticulation was performed and the marked surface area was quantified using an immersion digital microscribe, allowing a 3-dimensional virtual model of the articular surfaces to be assessed. Results: The median percentage of total accessible talonavicular articular surface area for the medial and dorsal approaches was 71% and 92%, respectively (Wilcoxon signed-rank test, P < .001). Conclusion: This study provides quantifiable measurements of the articular surface accessible by the medial and dorsal approaches to the talonavicular joint. Clinical Relevance: These data support for the use of the dorsal approach for talonavicular arthrodesis, particularly in cases where access to the lateral half of the joint is necessary.